Efficacy of a strength-based exercise program in patients with chronic tension type headache: a randomized controlled trial - Martín-Vera, Daniel; Sánchez-Sierra, Alberto; González-de-la-Flor, Ángel; García-Pérez-de-Sevilla, Guillermo; Domínguez-Balmaseda, Diego; del-Blanco-Muñiz, Jose Ángel (Frontiers in Neurology, 2023)
Background Strength-based exercise is widely used to treat tension-type headache, but the evidence of its benefit is unclear. This study aims to analyze the efficacy of a strength-based exercise program in patients with chronic tension-type headaches. Methods A randomized controlled trial with a 12-week strength-based exercise program, with chronic tension-type headache. The headache characteristics (which were the primary outcomes: frequency, duration, and intensity), cervical muscle thickness at rest or contraction of multifidus and longus-colli muscle, cervical range of motion, pain pressure threshold of temporalis, upper trapezius, masseter, tibialis muscle and median nerve, and cervical craniocervical flexion test were assessed at baseline and 12-weeks of follow-up in the intervention group (n = 20) and the control group (n = 20) was performed on 40 patients (85% women, aged 37.0 ± 13.3 years). Results Between baseline and week-12 of follow-up the intervention group showed statistically significant differences compared to control group in the following primary outcomes: duration and intensity of headaches. In addition, the intervention group improved the thickness of deep cervical muscles, reduced the peripheral sensitization, and improved the strength of deep cervical flexors. Conclusion A 12-week strength training of neck and shoulder region induced changes in pain intensity and duration, and physical-related factors in patients with TTH. Future interventions are needed to investigate if normalization of pain characteristics and physical factors can lead to an increase of headache-related impact.